G3P2A0 Hamil 30 Minggu Belum Inpartu dengan Partus Prematurus Imminens dan Riwayat Asma - Ratna Dewi PS; Kandita Mahran Nisa (CV. Jasa Sukses Abadi, 2020)
Imminent preterm is the presence of a threat in pregnancy with emergence signs in 20 weeks-37 weeks and the baby's birth weight is less than 2500 grams. Signs of diagnosis of imminent preterm such as contractions about 4 times in 20 minutes or 8 times in one hour and progressive changes in the cervix such as opening more than 1 cm, softening around 75-80% and even thinning of the cervix . Asthma is a chronic respiratory disorder that occurs due to breathing smooth muscle spasm, mucosal edema, and increased mucus secretion due to the response of allergens or excessive stimuli. Asthma in pregnancy is based on episodic symptoms in the form of airway flow obstruction, which is reversible or partially reversible. The severity of asthma can be classified as intermittent asthma, mild persistent asthma, moderate persistent asthma and severe persistent asthma, depending on the frequency and severity of symptoms, including night symptoms, episodes of attack and lung conditions. Some theories suggest the relationship of asthma with the occurrence of preterm labor. The theory is based on the similarity of the mechanism between the bronchial muscle and the myometrial muscle. Examples of theories proposed are the use of B-receptor stimulants that can relieve bronchospasm as well as can be used to delay preterm labor, such as the use of Salbutamol medication. In addition, Ca channel blockers that induce bronchodilation at the same time can also reduce uterine contraction activity. Prostaglandin F2α used in inducing labor can cause bronchoconstriction in subjects with a history of asthma and non-asthma.